2018
DOI: 10.13102/sociobiology.v65i2.2685
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Ascosphaera apis in Small-Scale Migratory Apis mellifera iberiensis Colonies

Abstract: Honey bee hives are moved yearly mainly for pollination, but also to take advantage of consecutive flowering events to get as many harvests of honey as possible and/or to find favorable sites for food sources and summer temperatures. Such movements may lead to pathogen spill-over with consequences on the honey bee health and finally on population decline. Ascosphaera apis is the causative agent of the chalkbrood disease, a pathology affecting honey bee larvae that significantly harms population growth and colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This study provides further insights into the impact of migratory beekeeping practices on honey bee health [ 35 , 36 ] and on the infestation rate of pathogens and diseases in the colonies [ 39 , 40 , 68 ]. Our major finding is that migratory beekeeping and its associated stress lead to higher V. destructor and N. ceranae infestation rates in the colonies, which partially confirms our initial hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides further insights into the impact of migratory beekeeping practices on honey bee health [ 35 , 36 ] and on the infestation rate of pathogens and diseases in the colonies [ 39 , 40 , 68 ]. Our major finding is that migratory beekeeping and its associated stress lead to higher V. destructor and N. ceranae infestation rates in the colonies, which partially confirms our initial hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Honey bee confinement, vibration and noise, and marked changes in colony temperature are among the negative influences on colonies associated with such practices. Moreover, the installation of colonies in new pollination locations might increase their exposure to pesticides [ 34 , 36 , 38 ] and pathogens [ 39 , 40 ]. These colonies must also adapt to new environmental conditions and potential stressors, including orientation cues, daily oscillations in temperature, humidity, and wind regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The most important fungal infection in honey bees is defined as Ascosphaeriosis (Chalkbrood Disease) [40] . It is reported that chalkbrood disease is very common in the world and in our country and seriously damages the production of bee products [41] . Although the findings obtained from our study are lower than the rates stated by Soysal and Gürcan [42] , it has been observed that the agent has continued its existence in the region for at least 9 years and threatened hive and bee health.…”
Section: Discussionmentioning
confidence: 99%
“…The movement to new pollination locations forces the colonies to adapt to new environmental conditions, including daily oscillations in temperature, humidity, and wind patterns. Additionally, their exposure to pathogen might increase, and infections by new pathogens may occur 39,40 . In fact, transportation and pollination services have recently been proposed to increase the infestation rate and abundance of Nosema ceranae and some viruses [27][28][29][30][31]37 in A. mellifera worker bees.…”
Section: Introductionmentioning
confidence: 99%